Chapter 8 Sense of Belonging in a Digitalised Care Work Community - Tammelin, Mia (Taylor & Francis, 2022)
This chapter uses the theoretical framework of sense of belonging to explore how eldercare workers from Finnish service housing units for older people describe the use of digital devices and applications in their work and the work practices that relate to their sense of belonging. The study is based on interview data (n = 25) that was collected in 2018 for a study on digitalisation of eldercare. The chapter asks: what does a sense of belonging mean for care workers' agency in a digital era? The analysis concentrates especially on the practices of belonging and how they are enacted in a digitalised work environment. The chapter proposes that in the digital era, a sense of belonging is particularly fluid and dynamic, and that it is constructed in the daily practices of work.